Clarifying the Misconceptions about Islamic Restrictions on Entertainment and Performing Arts in Malaysia - Mohd Sharizam, Bin Hamzah (AENSI Publisher, 2015)
Background: Muslims as a community have had issues and debates whether entertainment and Performing Arts are permissible in Islam. While some orthodox Muslims today totally ban any type of Performing Arts, claiming it’s haram (forbidden) and shun themselves, others have argued that Muslims are allowed to have some entertainment with some guideline from the Holy Quran and Hadith (words from Prophet Muhammad passed down). This paper was part of a project/research to see how the Muslim community misunderstood this issue with arguments from the Quran and Hadith. It is hoped that this research will contribute to the political debate and confusion on the subject in Malaysia and the country’s arts and culture policy. Whilst the study is focused on Malaysia, the study also hopes to foster a better understanding between non-Muslim and Muslim communities globally. Objective: The main objective of this research is to look at how Muslims misinterpreted passages from the Quran, while debating whether entertainment and Performing Arts is allowed in Islam or not. The second objective is to show examples how a moderate Muslim should assimilate with non-Muslim to foster more understanding and respect towards different religions. Results: In Malaysia, orthodox Muslims through the political Islamic party has managed to influence moderate Muslims to follow “their Muslim way” of practice. However, in recent years, Muslims in Malaysia through their scholars known as Ulama opened up on the discussion and debate towards this issue. In return, most of these scholars believed that Islam allows entertainment and Performing Arts as long as the guidelines in the Quran are followed. Conclusion: Islam allows entertainment with several historical incident were recorded in Hadith. However in Malaysia, Muslims scholars were divided into 2 different school of taught thus making them express this issue in different views. Muslim Sunnis which consist of more than 80% of the population Muslim community around the world including Malaysia are the most tolerance with many of them became scholars in various areas including entertainment business and Performing Arts.